2022
DOI: 10.1016/j.euo.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Meta-analysis Identifies Novel Genes Associated with Recurrence and Progression in Non–muscle-invasive Bladder Cancer

Abstract: Background: Non-muscle-invasive bladder cancer (NMIBC) is characterized by frequent recurrences and a risk of progression in stage and grade. Increased knowledge of underlying biological mechanisms is needed. Objective: To identify single nucleotide polymorphisms (SNPs) associated with recurrence-free (RFS) and progression-free (PFS) survival in NMIBC. Design, setting, and participants: We analyzed outcome data from 3400 newly diagnosed NMIBC patients from the Netherlands, the UK, Canada, and Spain. We generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Specifically, the combination of HLA-B07 and HLA-B44 homozygosity with CUETO is significantly correlated with intravesical recurrence. A meta-analysis by Galeshoot [ 90 ] searched for single nucleotide polymorphisms (SNPs) correlated with recurrence-free and progression-free survival in NMIBC. They found that lead SNP rs12885353 on chromosome 14 was associated with an increased expression of SCFD1 and associated with recurrence-free survival.…”
Section: Genomics Markersmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the combination of HLA-B07 and HLA-B44 homozygosity with CUETO is significantly correlated with intravesical recurrence. A meta-analysis by Galeshoot [ 90 ] searched for single nucleotide polymorphisms (SNPs) correlated with recurrence-free and progression-free survival in NMIBC. They found that lead SNP rs12885353 on chromosome 14 was associated with an increased expression of SCFD1 and associated with recurrence-free survival.…”
Section: Genomics Markersmentioning
confidence: 99%
“…Studies evaluating the genetic markers such as NMP22 [ 83 ] and DNA methylation [ 84 , 85 , 86 ] have good results with a sensitivity ranging from 0.615 to 0.94, the highest found in [ 86 ] for ZNF154 methylation. Eight statistical studies [ 70 , 74 , 78 , 79 , 87 , 88 , 89 , 90 ] found a correlation of multiple genetic markers with recurrence but did not evaluate test performance characteristics. Some of the markers were strongly correlated with the tumor stage and grade, such as Circ-ZKSCAN1 [ 78 ].…”
Section: Genomics Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of non-muscle invasive bladder cancer (NMIBC) involves approximately 75% of incident cases of bladder cancer [ 1 , 2 ], and the frequent reoccurrence and progression may lead to more lethal muscle-invasive bladder cancer (MIBC) [ 3 ]. Subsequently, the quest for frequent surveillance episodes and continuous treatment systems became an urgent necessity to combat NMIBC reoccurrence and their progression in the human body [ 4 ]. Surgical intervention, immunotherapy, photodynamic therapy, chemotherapy, and radiotherapy are all effective treatments for patients suffering from bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…2 , 16 - 19 A recent genome-wide meta-analysis that investigated the outcomes of non–muscle-invasive UBC identified rs12885353 (near SCFD1 ), which is significantly associated with UBC recurrence-free survival. 20 Most of these variants and genes confer modest increase in UBC risk (odds ratio < 2) and aggregate in xenobiotic metabolism, DNA repair, and cell cycle progression pathways. 21 …”
Section: Introductionmentioning
confidence: 99%